The close binary fraction as a function of stellar parameters in APOGEE: a strong anticorrelation with α abundances. Issue 2 (23rd September 2020) - Mazzola, Christine N; Badenes, Carles; Moe, Maxwell; Koposov, Sergey E; Kounkel, Marina; Kratter, Kaitlin; Covey, Kevin; Walker, Matthew G; Thompson, Todd A; Andrews, Brett; Freeman, Peter E; Anguiano, Borja; et al.
ABSTRACT: We use observations from the Apache Point Observatory Galactic Evolution Experiment (APOGEE) survey to explore the relationship between stellar parameters and multiplicity. We combine high-resolution repeat spectroscopy for 41 363 dwarf and subgiant stars with abundance measurements from the APOGEE pipeline and distances and stellar parameters derived using Gaia DR2 parallaxes from Sanders & Das to identify and characterize stellar multiples with periods below 30 yr, corresponding to ΔRVmax  ≳ 3 km s −1, where ΔRVmax is the maximum APOGEE-detected shift in the radial velocities. Chemical composition is responsible for most of the variation in the close binary fraction in our sample, with stellar parameters like mass and age playing a secondary role. In addition to the previously identified strong anticorrelation between the close binary fraction and [Fe/H],  we find that high abundances of α elements also suppress multiplicity at most values of [Fe/H] sampled by APOGEE. The anticorrelation between α abundances and multiplicity is substantially steeper than that observed for Fe, suggesting C, O, and Si in the form of dust and ices dominate the opacity of primordial protostellar discs and their propensity for fragmentation via gravitational stability. Near [Fe/H] = 0 dex, the bias-corrected close binary fraction ( a < 10 au) decreases from ≈100 per cent at [α/H] = −0.2 dex to ≈15 per cent near [α/H] = 0.08 dex, with a suggestive turn-up to ≈20 per cent near [α/H] = 0.2. We conclude that the relationship between stellar multiplicity and chemical composition for sun-like dwarf stars in the field of the Milky Way is complex, and that this complexity should be accounted for in future studies of interacting binaries.